The Meaning of Studying Batik Art to Create Character Education in Cultural History - Muhammad Rico; Dewicca Fatma Nadilla (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The aim of writing this article is to analyze the importance of studying Batik art in order to create character in cultural history, which is important to prevent moral degradation in young people. The research method used is a literature study prepared in the same way as other studies; however, data was collected through library sources by reading, taking notes, and analyzing research materials from papers about the variables studied. The results of the research show changes in the use of Batik art in ancient times and now, which in the past was only used by the kings and their families, which is different from now which can be used by all groups and other regions also have batik with their own regional characteristics. Character education includes education on values, manners, morals and character which aims to develop students' ability to make good and bad decisions, maintain the good and realize that goodness in everyday life wholeheartedly, considering how important the scope of character education is, it is a The character education process must include the totality of students' potential, both in cognitive, affective and psychomotor aspects.